2008
DOI: 10.1113/jphysiol.2008.153817
|View full text |Cite
|
Sign up to set email alerts
|

Offspring from mothers fed a ‘junk food’ diet in pregnancy and lactation exhibit exacerbated adiposity that is more pronounced in females

Abstract: We have shown previously that a maternal junk food diet during pregnancy and lactation plays a role in predisposing offspring to obesity. Here we show that rat offspring born to mothers fed the same junk food diet rich in fat, sugar and salt develop exacerbated adiposity accompanied by raised circulating glucose, insulin, triglyceride and/or cholesterol by the end of adolescence (10 weeks postpartum) compared with offspring also given free access to junk food from weaning but whose mothers were exclusively fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
160
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(178 citation statements)
references
References 23 publications
14
160
4
Order By: Relevance
“…Further support for generation of obesity in the offspring of obese dams comes from Bayol et al, who showed that offspring of rats that were fed a 'junk food' diet (including highly palatable foods such as chocolate, crisps and doughnuts) in pregnancy and lactation developed increased fat mass after weaning on to a normal diet [35,36]. In contrast to the present study, this was more predominant in females than males [35].…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Further support for generation of obesity in the offspring of obese dams comes from Bayol et al, who showed that offspring of rats that were fed a 'junk food' diet (including highly palatable foods such as chocolate, crisps and doughnuts) in pregnancy and lactation developed increased fat mass after weaning on to a normal diet [35,36]. In contrast to the present study, this was more predominant in females than males [35].…”
Section: Discussioncontrasting
confidence: 51%
“…Using an identical diet to that of the present study, we have also recently shown a similar increase in fat mass in the offspring of obese mice, proving commonality of this model in different rodent species [34]. Further support for generation of obesity in the offspring of obese dams comes from Bayol et al, who showed that offspring of rats that were fed a 'junk food' diet (including highly palatable foods such as chocolate, crisps and doughnuts) in pregnancy and lactation developed increased fat mass after weaning on to a normal diet [35,36]. In contrast to the present study, this was more predominant in females than males [35].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Rats with prenatal-only exposure were fatter than those without any exposure, but rats that were exposed to junk food throughout the study had the riskiest outcomes, including the highest levels of adiposity and hyperinsulinemia. 46 In a similar 2 Â 2 experimental design, offspring of dams fed high-fat chow during pregnancy had higher adult body weights and blood pressure than offspring who experienced a standard maternal diet in utero, but rats experiencing effects of high-fat diets in utero and during suckling showed the greatest body mass and highest blood pressure, as well as hyperinsulinism and hyperleptinemia as adults. The epigenetic processes that begin with maternal obesity have a greater impact on those who are already genetically susceptible to obesity.…”
Section: Prenatal Periodmentioning
confidence: 96%
“…However, in the Bayol study, insulin receptor expression was increased by cafeteria feeding at any stage of life in males and Irs2 was down-regulated by cafeteria diet in females. Effects of the diet on expression of PPARg and glucose transporters in adipose tissue were also reported (Bayol et al 2008). The differences between the current study and the work by Bayol and colleagues are most likely to be explained by variation in the nature of the cafeteria feeding regimens and different timing of exposure (control over litter size and variety of cafeteria foods offered).…”
Section: A B C D E Fmentioning
confidence: 97%